Phase‐Selective Synthesis of Ruthenium Phosphide in Hybrid Structure Enables Efficient Hybrid Water Electrolysis Under pH‐Universal Conditions. Issue 20 (17th April 2022) - Qian, Qizhu; Wang, Wentao; Wang, Gongrui; He, Xiaoyue; Feng, Yafei; Li, Ziyun; Zhu, Yin; Zhang, Yangyang; Zhang, Genqiang
Abstract: Hydrazine‐assisted hybrid water electrolysis is an energy‐saving approach to produce high‐purity hydrogen, whereas the development of pH‐universal bifunctional catalysts encounters a grand challenge. Herein, a phase‐selective synthesis of ruthenium phosphide compounds hybrid with carbon forming pancake‐like particles (denoted as Rux P/C‐PAN, x = 1 or 2) is presented. The obtained RuP/C‐PAN exhibits the highest catalytic activity among the control samples, delivering ultralow cell voltages of 0.03, 0.27, and 0.65 V to drive 10 mA cm −2 using hybrid water electrolysis corresponding to pH values of 14, 7, and 0, respectively. Theoretical calculation deciphers that the RuP phase displays optimized free energy for hydrogen adsorption and reduced energy barrier for hydrazine dehydrogenation. This work may not only open up a new avenue in exploring universally compatible catalyst to transcend the limitation on the pH value of electrolytes, but also push forward the development of an energy‐saving hydrogen generation technique based on emerging hybrid water electrolysis. Abstract : The phase‐selective synthesis of ruthenium phosphide (RuP) compounds hybridize with carbon forming a pancake‐like structure (RuP/C‐PAN), which displays highly efficient and robust hybrid water electrolysis for energy‐saving hydrogen production under pH‐universal conditions.